Maoa and Maob polymorphisms and personality traits in suicide attempters and healthy controls: a preliminary study. (March 2017) - Balestri, Martina; Calati, Raffaella; Serretti, Alessandro; Hartmann, Annette M.; Konte, Bettina; Friedl, Marion; Giegling, Ina; Rujescu, Dan
Abstract: Serotonergic neurotransmission dysfunctions have been well documented in patients with suicidal behaviour. We investigated monoamine oxidase A (MAOA: rs2064070, rs6323, rs909525) and B (MAOB: rs1799836, rs2311013, rs2205655) genetic modulation of personality traits (Temperament and Character Inventory, TCI) as endophenotype for suicidal behaviour. 108 suicide attempters and 286 healthy controls of German origin were screened. Among females, allelic analyses revealed associations between MAOA rs6323 A allele and higher Harm Avoidance in suicide attempters and MAOB rs2205655 A allele and higher Cooperativeness scores in healthy controls. Among males, MAOA rs909525 A allele was associated with higher Reward Dependence in suicide attempters. Multivariate analyses controlling for age and educational level mainly confirmed results. Case-control analyses in this subsample do not differ from our previously reported one. Despite of the small sample size, a possible involvement of these genes in the modulation of personality traits closely related to suicidal behaviour cannot be excluded. Highlights: Monoaminergic neurotransmission dysfunctions have been documented in patients with suicidal behaviours with contrasting results. The use of endophenotype, such as personality traits, may help in the dissection of the genetic underpinning of suicide. Among females, MAOA rs6323 was associated with Harm Avoidance in suicide attempters and MAOB rs2205655 was associated with Cooperativeness in healthy controls. Among males, MAOA rs909525 was associated with Reward Dependence in suicide attempters. MAOA and MAOB seemed to be involved in the modulation of personality traits closely related to suicidal behaviour.